A shape memory alloy based on photodiode for optoelectronic applications - Aldirmaz, E.; Guler, M.; Guler, E.; Dere, A.; Tataroglu, A.; Al-Sehemi, Abdullah G.; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2018)
A photodiode was fabricated as a Schottky contact using Cu-Al-Mn shape memory alloy and p-Si substrate. The alloy was characterized by some characterization techniques such as (SEM), XRD and DSC. The electrical and photovoltaic properties of the prepared Schottky diode were investigated under various illumination intensities and frequencies. The illumination dependent I-V measurements showed that the diode exhibited a photovoltaic behavior. The electronic parameters of the diode were obtained using various theoretical models. The photo transient behavior of the diode was analyzed under solar light. The admittance measurements indicate that the diode exhibits a dispersive capacitance behavior. The results indicate that the Schottky diode could be used in optic device applications. (c) 2018 Elsevier B.V. All rights reserved.
Keywords: Schottky diode; Shape memory alloy; Illumination effect